À propos de la liberté de navigation sur les fleuves internationaux: L’Affaire de l’Oder devant la Cour permanente de Justice internationale - Gadkowski, Andrzej (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2013)
The aim of the article is to present the issue of the freedom of navigation on international rivers in the context of the Oder case brought before the Permanent Court of International Justice in 1929 – a case of utmost importance for the development of the law of international watercourses and contemporary international law applicable to water resources. The author analyses the provisions of the Treaty of Versailles which declared the Oder to be an international river and put it under the jurisdiction of an international commission. The territorial jurisdiction of the International Commission of the River Oder was disputed between Poland and Germany, leading to the aforementioned proceedings before the PCIJ. The author presents the arguments put forward by both parties, the legal context of the case – in particular the provisions of the Treaty of Versailles and of the Barcelona Convention – and analyses the Court’s judgment. An analysis of the judgment is carried out, having recourse to the main concepts of the law of international watercourses.